Pancreatic Cancer Cells Isolated from Muc1-Null Tumors Favor the Generation of a Mature Less Suppressive MDSC Population - Kidiyoor, Amritha; Schettini, Jorge; Besmer, Dahlia M.; Rego, Stephen L.; Nath, Sritama; Curry, Jennifer M.; DasRoy, Lopamudra; Dreau, Didier; Mukherjee, Pinku (Frontiers in Immunology, 2014)
Mucin 1 (MUC1) is a transmembrane mucin glycoprotein that is over-expressed and aberrantly glycosylated in >80% of human pancreatic ductal adenocarcinoma (PDA) and is associated with poor prognosis. To understand the role of MUC1 in PDA, we have recently developed two mouse models of spontaneous PDA, one that expresses full-length human MUC1 transgene (KCM mice) and one that is null for MUC1 (KCKO mice). We have previously reported that KCM mice express high levels of myeloid derived suppressor cells (MDSCs) in their tumors and develop highly aggressive PDA. To further understand the underlying mechanism for high MDSC levels in KCM tumors, we generated primary cell lines from KCM and KCKO tumors. In this study, we report that MDSCs derived using KCM cells express significantly higher levels of arginase 1 and inducible nitric oxide synthase (markers associated with immune suppression) and lower levels of CD115 (a marker associated with maturation of myeloid cells) as compared to KCKO-derived MDSCs. Functionally, KCM-derived MDSCs secrete significantly higher levels of urea and nitric oxide when co-cultured with normal splenic cells as compared to KCKO-derived MDSCs. Data indicates that KCM-derived MDSCs remain immature and are more suppressive as compared to KCKO-derived MDSCs. This was further corroborated in vivo where MDSCs isolated from KCM-tumor bearing mice retained their immature state and were highly suppressive as compared to MDSCs derived from KCKO-tumor bearing mice. Finally, we show that KCM cells secrete significantly higher levels of prostaglandin E2 (PGE2,), a COX-2 metabolite and a known driver of suppressive MDSCs as compared to KCKO cells. Thus, inhibiting PGE2 with a specific COX-2 inhibitor reverses the immunosuppressive and immature phenotype of KCM-derived MDSCs. This is the first report that clearly suggests a functional role of pancreatic tumor-associated MUC1 in the development of functional MDSCs.